(untitled) (University of Khartoum Engineering Journal, 2022)
The objective of this study is to monitor the effect of storing, handling and adding chemical improvers on bread’s shelf life, through studying the change on bread’s quality parameters (taste, color, odor and texture) with time. Two types of bread (A and B) were baked; one with additionof chemicals (Banda Mixture of Enzyme and Additive(to its original ingredients(flour, yeast, sugar, salt and water)and the other without. Both types were bakedat 260 0C at the bakery of Food Research Center, Khartoum _ Each type of bread was stored using three modes of storage:(1) open plastic bag (2) closed plastic bag (3) paper bag.Hence there were six samples (A1, A2, A3, B1, B2, B3). The samples were evaluated by 9 semi-trained tasters for 24 hours at 8hours’ intervals. The test results of the six samples were analyzed statistically using SPSS software version 16.00. The study concluded that the chemically improved bread (sample A) is better than the unimproved one (sample B) as it maintained its taste, color, odor, and texture over time. In terms of shelf life, paper bags provide relatively better quality for short period while plastic bags provide better shelf life for longer period.